ANALISIS PENGARUH CADANGAN DEVISA, KURS DOLLAR AMERIKA DAN INFLASI TERHADAP NILAI EKSPOR FURNITURE DI INDONESIA - DEWI, NI WAYAN BELLA ASTIKA; DEWI, NI PUTU MARTINI (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 11. Nopember 2017(pp.2103-2351), 2017)
The purpose of this study was to determine the effect of foreign exchange reserves, US dollar exchange rate and inflation on the value of furniture exports in Indonesia. This research was conducted in Indonesia. The research object covering foreign exchange reserves, US dollar exchange rate, inflation and exports furniture in Indonesia. Results showed foreign exchange reserves and US dollar exchange rate and a significant positive effect on exports, while inflation is negative and significant effect on exports. That is, if the foreign exchange reserves and US dollar exchange rate rise, exports will also rise, and if inflation rose then exports will decline. Suggestions from this study is that the government is expected to maintain forests in Indonesia to ensure that manufacturers only take raw materials from plantations instead of natural wood. Keywords : foreign exchange reserves, US dollar exchange rate, inflation, exports.